Campaigning Online and Offline: Different Ballgames? : Presidentialization, Issue Attention and Negativity in Parties’ Facebook and Newspaper Ads in the 2019 Belgian General Elections - Lefevere, Jonas; Van Aelst , Peter; Peeters, Jeroen (Politics of the Low Countries, 2025)
This Research Note investigates party advertising in newspapers and on social media (Facebook) during the 2019 general elections in Flanders, the largest region of Belgium. The 2019 elections saw a marked increase in the use of social media advertising by parties, whereas newspaper advertising saw a decline. Prior research that compares multiple types of advertising, particularly advertising on social and legacy media remains limited. As such, based on a quantitative content analysis we investigate not just the prevalence of party advertising on both types of media, but also compare the level of negativity, presidentialisation, and issue emphasis. Our analysis reveals substantial differences: we find that not only the type of advertisements varies across the platforms, but also that social media ads tend to be more negative. Finally, parties’ issue emphasis varies substantially as well, with different issues being emphasized in newspaper and Facebook advertisements.